Business resilience in the pandemic and beyond Adaptation, innovation, financing and climate action from Eastern Europe to Central Asia - European Investment Bank (European Investment Bank, 2022)
COVID-19 set new challenges for the economies in Eastern Europe and Central Asia. Strong policy and fiscal support allowed businesses to stay afloat, with firms making long strides in innovation and in becoming global suppliers. This report examines the pandemic's business impact, trade and innovation, green economy and the financial gaps in this region. The report's analysis is based on the EBRD-EIB-WBG Enterprise Survey 2019, covering over 28 000 registered firms, and the first round of the COVID-19 Follow-up Enterprise Surveys, with over 16 000 firms.